An Open-Label, Investigator-Initiated, Single-Centre Pilot Study to Determine the Safety and Efficacy of Tofacitinib in Resistant Chronic Spontaneous Urticaria - Abhishek De; Shrayan Pal; Sushil Singh; Disha Chakroborty; Kiran Godse (Wolters Kluwer Medknow Publications, 2024)
Background: Chronic spontaneous urticaria (CSU) is a distressing skin condition characterized by the recurrent appearance of itchy hives. A subset of CSU patients remains resistant to conventional treatment with high-dose antihistamines. Tofacitinib, a Janus kinase inhibitor, has shown promise in various inflammatory skin diseases. We aimed to evaluate the efficacy of oral tofacitinib in patients with CSU resistant to antihistamines. Methods: This study examined data retrospectively from seven patients who were diagnosed with CSU and were treated with tofacitinib for at least six months. These patients initially exhibited resistance to treatment with four-fold up-dosed antihistamines. One of the patients was already on omalizumab, and another was tried on cyclosporine. The patients were administered oral tofacitinib at a dosage of 5 mg twice daily for six months. Patients were followed up monthly for disease control and side effects. The response to treatment was evaluated using the urticaria activity score over 7 days (UAS7) and urticaria control test (UCT). Paired t-tests were conducted to determine the statistical significance of the results using SPSS version 25 software. Results: Six out of the seven patients demonstrated a significant improvement in both UAS7 and UCT scores after six months of treatment with oral tofacitinib. The mean UAS7 score decreased from 24.86 at baseline to 3.83 at the study endpoint (P < 0.0001). Similarly, the mean UCT score increased from 0.57 at baseline to 14 at the study endpoint (P < 0.0001). The standard deviations for both measures were 4.85 and 0.98 at baseline and 3.1 and 3.1 at the study endpoint for UAS7 and UCT, respectively. Conclusion: In this six-month follow-up study, oral tofacitinib demonstrated significant efficacy in treating CSU patients' resistant to high-dose antihistamines. Most patients experienced a remarkable reduction in urticaria activity and an improvement in disease control. These findings suggest that tofacitinib holds promise as a potential therapeutic option for this challenging subset of CSU patients. However, larger, randomized controlled trials are warranted to further investigate the long-term safety and effectiveness of tofacitinib in this population.